Fishery, biology and stock assessment of carangid resources from the Indian seas - Reuben, S; Kasim, H Mohamad; Sivakami, S; Nair, P N Radhakrishnan; Kurup, K N; Sivadas, M; Noble, A; Nair, K V Somasekharan; Raje, S G (Indian Journal of Fisheries, 2011)
The estimated landings of carangids in India during 1981-88 ranged between 37 345 tonnes and 135 529tOMes, whereas the percentage composition of carangids in the total fish landings ranged from 2.7 to 8.1. Theaverage annual catch and the percentage of carangids in the total marine fish landings were estimated at 74 080tonnes and 4.5% respectively. Tamil Nadu (17.7%) and Andhra Pradesh (8.8%) from east coast and Keraia(34%), Kamatalca (17.6%) and Maharashtra (9.9%) from west coast yielded good catches of carangids.Megala.fpis cordyla, Decapterus ru.f.felli, Alepes kalla, Atropus atropu.f, Alepes djedaba, Atule mate,Caranx carangus and Seklroides leptolepis contributed significantly to the fisheries of different regions. Theresults of stock assessment and biology of the above species are presented. M. cordyla along east and northwestcoasts, D. ru.uelli along northwest coast. and C. carangu.f and S. leptolepis along Tamil Nadu coast are beingexploited expending much more effort than required to realize maximum sustainable yield (MSY). But D.ruuelli along east and southwest coast~ andA. kalla andA. djedaba along the Keraia coast can be exploited withincreased effort of trawl net to enhance their production to MSY level. Similar condition is exhibited by M.cordyla along southwest coast for drift gill net and A. mate along Kera1a coast for hooks and line.